On Enhancing Shareholder Control: A (Dodd‐) Frank Assessment of Proxy Access - COHN, JONATHAN B.; GILLAN, STUART L.; HARTZELL, JAY C. (Journal of Finance, 2016)
ABSTRACT We use events related to a proxy access rule passed by the Securities and Exchange Commission in 2010 as natural experiments to study the valuation effects of changes in shareholder control. We find that valuations increase (decrease) following increases (decreases) in perceived control, especially for firms that are poorly performing, have shareholders likely to exercise control, and where acquiring a stake is relatively inexpensive. These results suggest that an increase in shareholder control from its current level would generally benefit shareholders. However, we find that the benefits of increased control are muted for firms with shareholders whose interests may deviate from value maximization.